THE RELATIONSHIP BETWEEN EMOTIONAL AND AFFECTIVE DISORDERS AND COGNITIVE STATUS IN CHRONIC CEREBROVASCULAR PATHOLOGY - Djurabekova Aziza Tahirovna; Mamurova Mavlyuda Mirhamzaevna; Sulaimonova Mehriniso Muzafarovna (Scholar Express Journals, 2025)
Chronic cerebrovascular pathology is one of the leading causes of cognitive impairment in people over 50 years of age. The combination of cognitive dysfunction with emotional and affective disorders can significantly affect the course of the disease and the quality of life of patients, which determines the importance of studying their relationship.
Keywords: cognitive impairment; anxiety-depressive disorders; chronic cerebral ischemia